Prognostic potential of CK-19 managing disseminated oral squamous cell carcinomas in Pakistan: A descriptive cross-sectional study - Waqas Iqbal; Uzma Tariq; Arhama Surwaich; Surwaich Ali channa; Abdul Majid; Shan Ali; Naeem Bukhari (Journal of the Pakistan Medical Association, 2020)
A cross-sectional study was conducted to assess the adoptability of CK-19 as a routine diagnostic assay and potential prognostic marker following disseminated oral squamous cell carcinoma in Pakistani population. The current descriptive study was conducted at Isra Dental College Hospital, Isra University, Hyderabad, Pakistan. Suspected patients of oral squamous cell carcinomas (OSCC), who visited the Isra Dental College Hospital’s outpatient department from January 2014 up to January 2015 with four year follow up (from January 2015 up to December 2019), were included after ethical approval of the Institutional board. SPSS version 21.0 was used for data analysis. Sixty cases of oral squamous cell carcinoma (OSCC) were selected for CK-19 quantification by using PCR before and after incisional biopsy. Continuous...